Notational analysis in female grand slam tennis competitions - Sánchez-Pay, Alejandro (Array, 2021)
Grand Slam tennis tournaments are played on different surfaces. The aims of the present study were to analyse the technical differences in the Grand Slam tournaments (Australian Open or AO, Roland Garros or RG, Wimbledon or W, and the United States Open or US), as well as to establish differences between winning and losing players. A total of 580 sets in 248 matches played in Grand Slams between 2017 and 2018 were analysed. To observe differences between the tournaments, a one-way analysis of variance (Kruskal Wallis) with the Bonferroni post-hoc test was performed. Univariate (Wilcoxon test) analysis of data was carried out to show the differences between the winning and losing performances of sets.